The Concept of The Sīla’s Disparity in Determining The Results and Impacts of Its Observance: A Theravada Buddhist Approach (Social Science Review, 2025)
Sīla means moral discipline or ethical integrity. It is one of the main doctrines Buddhism advocates to sustain the path of well-being, peace, and liberation. The more a man engages himself in illicit deeds, the more he increases his suffering. Realizing human suffering, Gautama Buddha pioneered sīla as a way to relieve suffering. Buddhism posits that, akin to the rewards of virtuous actions, immoral actions yield repercussions. An escalation of malevolent actions will hinder spiritual emancipation and complicate the pursuit of tranquility. Consequently, the Buddha implored us to perform all virtuous deeds. The foundation of all virtuous activities is called sīla. This paper examines the advantages and disadvantages of violating sīla by analyzing its characteristics and categories. It primarily serves two functions: the ordinary and the extraordinary. The ultimate emancipation is the paramount objective of Buddhism, underscoring the significance of worldly existence. Sīla serves as the pathway to liberation and a mechanism for societal harmony. All Buddhist schools underscore the importance of sīla; yet this research examines discrepancies in the outcomes of sīla observance and the various issues investigated through a qualitative lens, drawing on the Theravada Buddhist Tipiṭaka.Social Science Review, Vol. 42(1), June 2025, pp. 163-187